Determinants of Foreign Investment in Indonesia Post-Pandemic - Sulvani, Putri; Fafurida, Fafurida (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: The Covid-19 pandemic brought out the phenomenon of a rapid increase in investment after it has ended in Indonesia. This study gives a significant contribution in analyze the impact of pandemic on foreign direct investment.Research Objectives: The aim of this research is to predict whether there is a relationship of interest rates, inflation, labor force, GDP, and exchange rate with investment.Research Methods: This research is also to examine the asymmetric relationship among variables using the NARDL (Nonlinear Autoregressive Distributed Lag) method to identify the long-run effects of these variables on the investment after the Covid-19 pandemic in Indonesia. It uses the secondary data from 1980-2022.Empirical Results: The results of research show that there is a long-run asymmetric effect of the variables of interest rates, GDP, and exchange rates on the foreign direct investment. It means that changes in these variable factors do not only affect the size of investment, but also the speed of its increase after the pandemic. Meanwhile, there is no asymmetric effect of the variables of labor force and inflation on the investment.Implications: This research provides a picture and new insights related to the foreign direct investment dynamics in Indonesia after the Covid-19 pandemic. This study implies that require a different policy approach in an effort to increase the investment in Indonesia.JEL Classification: F21, O40